AI could help us keep outdated computer programs working. - Sparkes, Matthew (New Scientist, 2024)
Artificial intelligence (AI) may be able to help maintain or replace outdated computer programs written in the COBOL computer language, which is still vital to some banks, airlines, and government departments. Many of these programs are composed of millions of lines of undocumented code, making it difficult to find competent engineers to update or replace them. Researchers have been training an AI model called XMainframe to interpret and rewrite COBOL code in other programming languages. While AI won't be able to replace human coders, it can accelerate their work and help migrate these systems to newer technology. However, some experts are skeptical about the reliability and autonomy of AI-generated code and believe that human programmers will always be necessary.